The optimal treatment approaches and prognostic factors in elderly patients with advanced stage biliary tract tumors - Göktaş Aydın, Sabin; Çakan Demirel, Burçin; Bilici, Ahmet; Yılmaz, Cansu; Topçu, Atakan; Aykan, Musa Barış; Kahraman, Seda; Atcı, Muhammed Mustafa; Akbıyık, Ilgın; Akgül, Fahri; Ölmez, Ömer Fatih; Aydın, Ahmet (Ankara Hematology Oncology Association, 2023)
Introduction: There is a lack of evidence of the outcomes in elderly patients advanced stage biliary tract cancer due to the patients aged over 65 years are less than 25% in many prospective trials. We designed a retrospective multicenter study to evaluate the factors affecting treatment and survival in elderly patients with advanced-stage biliary tract cancer. Materials and methods: A total of 116 patients with advanced stage biliary tract cancer aged ?65 years were included, and the treatment responses, survival, and toxicity rates were evaluated with respect to age groups Results: There was no significant difference between age and response to treatment, survival, or toxicity. The median progression-free survival and overall survival were 5.3, and 11.8 months respectively. Multivariate analysis indicated that ECOG PS (p<0.001 CI95% 1.5-3.7) and PNI (p<0.001 CI 95% 0.14-0.41) were significant independent prognostic factors for PFS. The independent prognostic factors for OS were choice of frontline regimen, NLR and PNI (p=0.007 CI 95% 0.71 – 0.94, p=0.006 CI 95% 1.2 – 3.1, p=0.001 CI 95% 0.35 – 0.91, respectively). Discussion: This study confirms the general prognostic relevance of inflammatory parameters and the importance of frontline treatment in elderly patients with advanced-stage biliary tract tumors. Additionally, getting older does not indicate that treatment will be avoided or that they will have a worse prognosis and suffer from more toxicities.

Giriş: 65 yaş üzeri hastaların klinik çalışmaların %25’inden daha azını oluşturması nedeniyle biliyer sistem kanseri olan ileri yaş hastaların yönetimi konusunda kanıt eksiği bulunmaktadır. Bu amaçla, metastatik safra yolu kanseri tanılı yaşlı hastalarda tedaviyi ve sağkalımı etkileyen faktörleri değerlendirmek için retrospektif çok merkezli bir çalışma tasarladık. Gereç ve yöntemler: Çalışmaya 65 yaş ve üzeri, ileri evre safra yolu kanseri tanısı almış, 116 hasta dahil edildi ve yaş gruplarına göre tedavi yanıtları, sağkalım ve toksisite oranları değerlendirildi. Bulgular: Median yaşa göre gruplandırılıdğında; yaş ile tedaviye yanıt, sağkalım, toksisite arasında anlamlı bir fark bulunmadı. Tüm populasyonda medyan progresyonsuz sağkalım (PSK) ve genel sağkalım (GSK) sırasıyla 5.3, 11.8 aydı. Multivariate analizde, PSK için bağımsız prognostik faktörler preformans durumu(ECOG PS) (p<0.001 CI95% 1.5-3.7) ve Prognostik nutrisyonel indek (PNI) (p<0.001 CI 95% 0.14-0.41) olarak bulundu. GSK için ise bağımsız prognostik faktörler, birinci sıra tedavi seçimi, Notrofil Lenfosit oranı (p=0,007 CI %95 0,71 – 0,94) ve PNI (p=0,001 CI %95 0,35 – 0,91) olarak bulundu. Tartışma: Metastatik safra yolu kanseri olan yaşlı hastalarda prognozu etkileyen temel faktöreler inflamatuar parametreler ve birinci basamakta seçilen kemoterapi rejimidir. İleri yaş ile sağkalım, toksiste profili ve tedavi toleransı farklılık göstermemektedir.
Metastatik safra yolu kanseri olan yaşlı hastalarda optimal tedavi yaklaşımları ve prognostik faktörler
Keywords: Biliary Tract Cancer; Elderly Population; Prognostic Nutritional Index; Systemic Inflammatory Index; Safra Yolu Kanseri; Yaşlı Populasyon; Prognostik Nutrisyonel İndeks; Sistemik İnflamatuvar İndeks